(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
Fifty exotic rice genotypes along with two check varieties were studied to measure the variability among the genotypes for yield and yield contributing characters, estimate genetic parameters, association among the characters and their contribution to yield. High genotypic co-efficient of variation (GCV) was observed for days to 50% flowering, days to first flowering and spikelet sterility whereas low genotypic co-efficient of variation (GCV) was observed for grain length and filled grains per panicle. High heritability with high genetic advance in percent of mean was observed for days to 50% flowering and pollen sterility indicated that this trait was under additive gene control and selection for genetic improvement for this trait would be effective. On the other hand, high heritability with low genetic advance in percent of mean was observed in days to harvesting and grain length which indicated that non-additive gene effects were involved for the expression of this character and selection for such trait might not be rewarding. Correlation studies revealed that highest significant positive association of grain yield was with days to first flowering, days to harvesting, filled grains per panicle followed by grain length at genotypic and phenotypic level. Path co-efficient analysis revealed that maximum direct contribution towards grain yield with days to harvesting followed by filled grains per panicle. DOI: http://dx.doi.org/10.3329/bjpbg.v25i1.17009